Protective effect of betaine against skeleton muscle apoptosis in rats induced by chronic alcohol and statin consumption - Ilhan, Oglakci A.; Ozkoc, M.; Ol, Kusat K.; Karimkhani, H.; Senturk, H.; Burukoglu, D.; Kanbak, G. (COMENIUS UNIV, 2020)
AIM: The aim of the present study was to investigate the effect of apoptosis on rat skeletal muscle caused by chronic alcohol and statin consumption with modified liquid diet and to elucidate protective effects of betaine supplementation. METHODS: TNF-alpha (tumor necrosis factor), NF-kappa B (Nuclear Factor kappa B), cytochrome c and caspase-3 levels with or without betaine treatment in alcohol and/or statin-induced skeleton muscle apoptosis rats as well as in controls were measured in serum and tissue. Histologic examinations of the muscle tissues were also performed. RESULTS: In our study, betaine treated treatment groups we found that calpain and caspase activities and cytokine c release were decreased caused by alcohol, statin and more importantly alcohol+statin group and TNF and NF-kappa B levels were also close to the levels of control group. Similarly, significant improvements have been observed in our morphological and histological examination results also supporting our biochemical data. CONCLUSION: We found that combined consumption of ethanol and statin is capable of triggering apoptotic cell death in rat muscles more than the consumption of only alcohol or only statin. Betaine was able to reduced this muscle cell death induced by alcohol and/or statin consumption (Tab. 4, Fig. 4, Ref. 43). Text in PDF www.elis.sk
Keywords: alcohol; statin; rat; muscle; apoptosis; FACTOR-KAPPA-B; ACTIVATION; BRAIN; ISCHEMIA; MYOPATHY; General & Internal Medicine